1965
DOI: 10.1029/wr001i004p00577
|View full text |Cite
|
Sign up to set email alerts
|

Some operating characteristics of a rapid response tensiometer system

Abstract: An experimental arrangement for measuring soil‐water suctions with rapid response is described and the operating characteristics of the tensiometer‐transducer system discussed. The equations relating to the response of the equipment are given, and a dynamic correction procedure using an iterative approach is illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…This conveys the double advantage of avoiding correction methods for a hydrostatic capillary pressure distribution required in a conventional retention cell [e.g., Jalbert and Dane , 2001], while simultaneously providing a known gradient to the nonwetting fluid for the determination of k rN . Sequential steady state flow conditions (i.e., constant P C and constant NWP flux for each established S W ) were achieved, in contrast to the published method, by fixing the wetting phase saturation at each step and monitoring the wetting phase pressures as they progress to equilibrium [ Watson , 1965]: a process which occurs in hours, rather than the converse which can take days.…”
Section: Methodsmentioning
confidence: 99%
“…This conveys the double advantage of avoiding correction methods for a hydrostatic capillary pressure distribution required in a conventional retention cell [e.g., Jalbert and Dane , 2001], while simultaneously providing a known gradient to the nonwetting fluid for the determination of k rN . Sequential steady state flow conditions (i.e., constant P C and constant NWP flux for each established S W ) were achieved, in contrast to the published method, by fixing the wetting phase saturation at each step and monitoring the wetting phase pressures as they progress to equilibrium [ Watson , 1965]: a process which occurs in hours, rather than the converse which can take days.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the system installed at the study site, together with associated field and laboratory tests, are fully reported in Anderson & Kneale (1980a) and Watson (1965). Twenty-two tensiometers were installed at various depths down to 2 m with a de-airing line terminating at the ground surface immediately above each tensiometer location.…”
Section: Pore Pressure Monitoringmentioning
confidence: 99%
“…Ideally, the redistribution of water within soil profiles should be assessed by measuring not only water contents but soil water pressures, thereby critically examining the hysteretic nature of the 0 versus p relation coupled with calculations of capillary conductivity. In the laboratory, the gamma radiation absorption method for measuring soil water and the recently developed pressure transducer technique [Watson, 1965] for instantaneously measuring soil water pressure distributions would allow the necessary data for computer solutions. The role of hysteresis under field conditions could be established by examining water content chan•es in situ.…”
Section: When a Continuous Air Phase Exists Within The Soil The Succmentioning
confidence: 99%